A case study on the performance of repaired sandwich composite aeronautical structures in different failure characteristics under bending loading. (July 2023) - Süsler, Sedat; Avşar, Yunus Emre; Türkmen, Halit S.
It is important to develop composite repair methods and investigate their performance against in-service and severe conditions due to high cost of composites, current environmental conscience and difficulties in composite recycling. In this study, the performance of various repair methods applied to two different types of polymer sandwich composite panels made of identical aramid honeycomb core, which are actively used in aerospace structures, is investigated. It is aimed to obtain different failure characteristics and to investigate the effects of these failure modes on the performance of repair methods for two different facesheet types. Three-point bending tests are configured for the flexural performance of repaired sandwich structures in the case of damage modes of core-facesheet adhesive bonded joint delamination and core damage and facesheet failure. The load carrying capacity is measured by calculating the ultimate value of core shear stress and facing stress. The results show that the configured three-point bending procedure is effective to analyse different span regions and to have various failure characteristics. The repaired samples succeed between 80% and 112% in the load capacity. It is proved that repaired specimens have higher load carrying capacity if facesheet based failure due to facing ultimate normal stress is occurred against delamination and core failure due to core shear stress. In addition to this, a modified epoxy filling/patch repair method for sandwich structures made of honeycomb core which can increase the load carrying capacity significantly is presented.